Design of Remote Power Management and Control Solution in IoT Device Environment - Kim, Bong-Hyun; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The existing remote power management and control solution is controlled from the outside through the internal router. That is, if there is an internal firewall, the access path is limited due to complicated network setting. In other words, there is a problem that connection can be limited because the hub server and the public IP address are required to access from the outside.Methods/Statistical analysis: There is a need for a way to build a remote control and power management system on the remote device itself. Thereby, the user does not need any additional setting for power management or control to the remote device. That is, there is a need for a remote power management and control solution capable of freely controlling power and control remotely in the Internet environment even if a firewall exists inside.Findings: In this paper, we manage and control the power of the target terminal remotely from the client terminal to the target terminal via the main server and the hub server. In addition, in the internal firewall environment, a remote terminal requests power to the target terminal via the server. Finally, the remote connection of the target terminal can be wired/wireless in the hub server, and the corresponding function is installed by installing separate hardware in the target terminal.Improvements/Applications: In this paper, we design a solution to remotely manage and control power in IoT device environment. This enables the development of a system that can reduce the energy efficiency of remote devices and eliminate standby power. It is a technology that provides a fundamental solution for remote power management in IoT environment by allowing users to turn on / off the computer or device at any time and remotely manage it.Â Â Â